Recepcja Eugeniusza Sue w Anglii połowy XIX wieku na podstawie monografii Berry Palmer Chevasco = The reception of Eugene Sue in mid -nineteenth century England on the basis of Berry Palmer Chevasco`s monograph - Gołębiowska, Urszula (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is a brief presentation of a thorough and exhaustive study of the reception of EugeneSue in Britain in the middle of the nineteenth century. "Mysterymania. The Reception of Eugene Suein Britain 1838-1860" by Berry Palmer Chevasco advances the thesis that despite a generally criticalattitude of the British literary establishment towards the French writer, his prose may have hada more significant impact on British writers than has been recognized.
Keywords: Sue, Eugene (pseud.), Sue, Marie-Joseph (1804-1857); Palmer Chevasco, Berry (1953 -); literatura angielska; 21 w.